Mass-spring modeling of the eardrum for surgical simulation - Ho, Andrew K.; Ladak, Hanif M. (CMBES Proceedings, 2010)
A virtual-reality simulator has been developed for the purpose of training surgical residents to perform myringotomy. Myringotomy is an operation which involves making an incision in the eardrum, primarily to treat middle-ear infections. This is the first procedure taught to ear, nose and throat residents and there is a high risk of error. Currently the virtual-reality environment draws a line on the eardrum when the virtual blade touches the simulated eardrum. This is the only visual feedback the trainee receives. Surgeons experienced with myringotomy have indicated that seeing the eardrum deform is an important visual cue indicating how far the blade has entered the middle-ear cavity. Our objective was to develop a deformable eardrum model that accurately responds to a trainee’s input in real time, and also to model the incisions that occur during a myringotomy. A mass-spring model of the eardrum has been developed which runs at 80 frames per second. A technique for determining spring constants from known mechanical properties has been applied. Displacements have been computed in response to point loads and have been compared with results from a finite-element model. Displacement patterns computed using the mass-spring model are similar to those computed using the finite-element model. The force-displacement curves obtained from the mass-spring model and the finite-element model both demonstrate nonlinearity in response with displacements growing less than in proportion to the applied force. Incision formation was achieved by re-aligning the mesh with the direction of the incision and then disconnecting springs. Keywords: Eardrum, mass-spring model, finite-element model, virtual reality, surgical simulator, myringotomy